Study on Performance of Infill Wall Masnory RCC Frame Using Alternative Types of Bricks: A Review - Joravia, Dhawal H.; Parikh, Kaushal B. (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2015)
The purpose of this literature review is to study the reduction of base shear and behavior of masonry in seismic loading and the evolution of interlocking brick methodologies and their different shapes. And also study Arrangement of infill walls with RCC frame in plan and elevation and base shear analysis using SAP2000 software. The study includes use of polymer material as make of polymer brick and study of availability of recyclable polymer material.